Chiral substituent containing perylene monoanhydride monoimide and its highly soluble symmetrical diimide: synthesis, photophysics and electrochemistry from dilute solution to solid state - Amiralaei, Sheida; Uzun, Duygu; Icil, Huriye (Springernature, 2008)
A new chiral perylene monoanhydride monoimide (1) with a sterically hindered chiral amine was successfully synthesized for further selective functionalization at terminal positions. At the same time., the chiral perylene diimide (2) with the same amine has been synthesized. The synthesized products were characterized using the data from NMR. 1R, MS, UV-vis, DSC, TGA, elemental analysis and cyclic and square wave voltammetry, Compound 2 shows all excellent solubility of 200 mg mL(-1) in chloroform. The band gap energy (E-g), LUMO and HOMO energy values were 2.28, -3.77 and -6.05 eV for 2, respectively in chloroform. In solid state, the band gal) energy (E-g), LUMO and HOMO energy values were 1.96, -4.22 and -6.18 eV for 1 and 1.92, -4.13 and -6.05 eV for 2, respectively. Whereas 1 (solid state: -0.58 and -0.69 V vs. ferrocene/ferrocenium couple) and 2 (in chloroform: -1.03 and -1.22 V vs. ferrocene/ferrocenium couple) show two reversible reduction steps, 2 exhibits only one reversible wave (solid state: -0.67 V vs. ferrocene/ferrocenium couple). The diffusion coefficients were determined as 1.91 x 10(-7) and 8.47 x 10(-7) cm(2) s(-1) for 1 and 2 in solid state, respectively, and 1.27 x 10(-5) cm(2) s(-1) for 2 in solution. The solid state emission ability of the chiral products (2 is much more emissive than 1) remains a challenge for photonic, electronic and sensor applications. I and 2 showed high thermal stability. Efficient prevention of intermolecular pi-pi contacts of fluorophores results in an excellent fluorescence emission in solid state and Solubility for 2.
Keywords: Optical-Properties; Bisimide Dyes; Systems; Model; Polyphenylene; Assemblies; Electrons; Transport; Ions